Sustainable Marketing: An Exploratory Study of the Perceptions of Marketing Managers in International Spanish Hotels - Costa, Gerard (Archīum Ateneo, 2014)
Sustainable marketing is one of the main challenges facing firms over the next few years because of its potential impact on both the growth of firms and the image of business people, hence the need for executives to manage its implementation. This article explores how hotel marketing managers in Spain perceive and manage the role of marketing in improving sustainable business management and the changes needed to make sustainable marketing work. The study contributes twenty-four empirical cases to discover what corporate changes managers consider necessary in order to make the hotel industry sustainable. The main research contribution is an initial framework of four fields in which executives set company management priorities with a view towards implementing sustainable marketing.